2021
DOI: 10.1111/vsu.13594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of the smallI‐Locinterlocking nail in 30 feline fractures: A prospective study

Abstract: Objective: To describe medium-term functional outcome after nail osteosynthesis in feline traumatology and report clinically relevant recommendations for I-Loc angle-stable interlocking nail use in cats. Study design: Prospective clinical study. Sample population: Client-owned cats (n = 29). Methods: Consecutive cases with femoral, tibial, or humeral fractures were included. Outcome measures included fracture and surgical procedure description, limb alignment, nail size vs body weight (BW), percentage of nail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 41 publications
(139 reference statements)
0
20
0
Order By: Relevance
“…Supracondylar fractures can be surgically challenging as even simple fractures may not have inherent rotational or shearing stability and the distal fragment is inevitably short. 100 While stabilisation with dynamic intramedullary cross-pinning has been described, 101 rigid stabilisation with a bone plate, external skeletal fixator or angle-stable interlocking nail 81 is recommended, with care being taken not to penetrate the stifle joint 99 or impinge patellar tracking.…”
Section: Distal Femoral Fracturesmentioning
confidence: 99%
See 4 more Smart Citations
“…Supracondylar fractures can be surgically challenging as even simple fractures may not have inherent rotational or shearing stability and the distal fragment is inevitably short. 100 While stabilisation with dynamic intramedullary cross-pinning has been described, 101 rigid stabilisation with a bone plate, external skeletal fixator or angle-stable interlocking nail 81 is recommended, with care being taken not to penetrate the stifle joint 99 or impinge patellar tracking.…”
Section: Distal Femoral Fracturesmentioning
confidence: 99%
“…89,91 In addition, clinical studies have reported the use of the I-Loc system in a wide variety of feline fracture configurations with good outcomes. 81,92 It should be noted that interlocking nails can be placed without the need for fluoroscopy as palpation of anatomical landmarks while flexing and extending the leg has been shown to be accurate for limb alignment; 22 Although external skeletal fixators are particularly well suited to non-reconstructable fractures, they can be applied to all fracture types. It is important to realise, however, that they tend to result in more intensive postoperative management, including more visits for radiographs as a decision has to be taken as to when to remove them, and they can lead to a series of minor complications, most commonly pin tract infections or pin breakages.…”
Section: Jfms Clinical Practice 453mentioning
confidence: 99%
See 3 more Smart Citations